-10+-8m=-110+6m

Simple and best practice solution for -10+-8m=-110+6m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10+-8m=-110+6m equation:


Simplifying
-10 + -8m = -110 + 6m

Solving
-10 + -8m = -110 + 6m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-6m' to each side of the equation.
-10 + -8m + -6m = -110 + 6m + -6m

Combine like terms: -8m + -6m = -14m
-10 + -14m = -110 + 6m + -6m

Combine like terms: 6m + -6m = 0
-10 + -14m = -110 + 0
-10 + -14m = -110

Add '10' to each side of the equation.
-10 + 10 + -14m = -110 + 10

Combine like terms: -10 + 10 = 0
0 + -14m = -110 + 10
-14m = -110 + 10

Combine like terms: -110 + 10 = -100
-14m = -100

Divide each side by '-14'.
m = 7.142857143

Simplifying
m = 7.142857143

See similar equations:

| g(x)=-6x-7 | | -7(6x+2)=-266 | | 7x+2=5x+(-2) | | 6(-9x+5)=-240 | | 7(x)-2=26 | | -6(-6x-10)=276 | | -16+4x=5(x-1) | | 16n^2+8n+1= | | x^4-3x^3+4x^2-7x+15=0 | | 7-7n+3n=11-92 | | -6x-2=12 | | -9(6x-16)=468 | | 5(-10x-13)=-415 | | ln(x-1)=2.3 | | 6(9x+17)=426 | | 0=3t^2-2t | | x=y^2+125y+120 | | 7x+2*-2=6 | | 9(6x+5)=-441 | | 7y+6=13 | | X+5*3-10=80 | | 7(-7x-9)=-504 | | 8y+5=77 | | -30x^4/6x | | 9(-5x+2)=-342 | | 6x/18x^6 | | 6(7x+2)=222 | | 18x^6/6x | | 84=-26+x | | 2b-72+b-30=180 | | [(m-1)/(m-1)]0 | | 4(x+3)-2x+8= |

Equations solver categories